Women's perceptions of their health, family and personal needs in a rural area : some implications for social work practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Work at Massey University - McIntyre, Ann (Massey University, 1987)
A democratic - socialist, feminist perspective was adopted to undertake an in-depth investigation of the social requirements and support needs of a group of 50 women living in the rural Far North. Critical health, family and community support service needs were identified using qualitative research techniques. An analysis of the information so derived highlighted a range of difficulties experienced by women living in the rural area. These difficulties included isolation, access, inequality, poverty, unemployment and pervasive sexist attitudes among key service providers. Certain conclusions were made, particularly with respect to the practice of social work in rural areas and the training of future social workers. It is also clear that further research into the consequences of inadequate social services in rural areas should be undertaken.
Keywords: New Zealand Northland; Women's health services; Women; Health and hygiene; Social work with women